Penerapan Media Congklak Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 04 Hadipolo - Sari, yuli Fani Mayang; Masturi, Masturi; Kironoratri, Lintang (Universitas Negeri Makassar, 2023)
The research aims to improve the learning outcomes of fourth grade students on the theme 7 The Beauty of Diversity in My Country, aspects of knowledge and skills aspects of learning Indonesian language and social studies at SDN 04 Hadipolo. This research uses Classroom Action Research method. The subjects used in this study were the fourth grade students of SDN 04 Hadipolo, totaling twenty five students. This research consists of two cycles. Data collection techniques in the form of interviews, observations, tests, and documentation. Data analysis in the form of qualitative and quantitative data analysis. The learning outcomes of students knowledge aspects of Indonesian language learning content increased quite significantly from cycle I (56%) to cycle II (84%). The improvement of student skill aspect learning outcomes in the first cycle (40%) to the second cycle to (76%). Based on the results of the study, it can be concluded that the application of Congklak media with the help of the unlucky card can improve student learning outcomes of fourth graders at SDN 04 Hadipolo.